2017
DOI: 10.1590/s0100-204x2017000800009
|View full text |Cite
|
Sign up to set email alerts
|

Digital soil mapping and its implications in the extrapolation of soil-landscape relationships in detailed scale

Abstract: -The objective of this work was to test the extrapolation of soil-landscape relationships in a reference area (RA) to a topographic map (scale 1:50,000), using digital soil mapping (DSM), and to compare these results to those obtained in similar studies previously conducted in Brazil. A soil survey in a 10 km 2 RA, using conventional mapping techniques (scale 1:10,000), was made in order to map a 678 km 2 physiographically similar area (scale 1:50,000) using DSM. The decision tree technique was employed to bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Camera et al (2017) achieved an OOB error of 8.6 %, which is comparable to the RF results in Dataset05. The results of OA are in the same range as those obtained by Taghizadeh-Mehrjardi et al (2012), Heung et al (2017), Wolski et al (2017), Pásztor et al (2018), andAfshar et al (2018), even though they used different approaches to build the dataset and process the data.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Camera et al (2017) achieved an OOB error of 8.6 %, which is comparable to the RF results in Dataset05. The results of OA are in the same range as those obtained by Taghizadeh-Mehrjardi et al (2012), Heung et al (2017), Wolski et al (2017), Pásztor et al (2018), andAfshar et al (2018), even though they used different approaches to build the dataset and process the data.…”
Section: Discussionmentioning
confidence: 58%
“…The OA was obtained from the confusion matrix and represents the total success classification of the model when applied to the validation subset. Kappa is an association measure used to describe the concordance level of the map unit prediction (Wolski et al, 2017) over the validation subset.…”
Section: Computational Operation and Methodsmentioning
confidence: 99%
“…There is evidence that the extrapolation of a mechanistic model to areas with similar characteristics and processes has more potential than the extrapolation of a statistical model, because the mechanistic model depends on cause–effect relationships, whereas the statistical model depends on associations. Several studies that used a statistical model for DSM explored the potential of extrapolation (Afshar, Ayoubi, & Jafari, 2018; Grinand, Arrouays, Laroche, & Martin, 2008; Wolski et al, 2017). However, the soil property predictions in these extrapolated areas were poor.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 334 studies, 263 presented cartographic scale and spatial resolution (pixel size) information used (Table 3); 38 studies were found incompatible with the planimetric PEC-PCD, since their pixel size is higher than that indicated at the cartographic scale. (Giasson et al, 2006) 2008 (Figueiredo et al, 2008) 2009 (Crivelenti et al, 2009) 2010 (Chagas et al, 2010); (Coelho and Giasson, 2010) (Höfig et al, 2014); (Teske et al, 2014) 2015 (Bagatini et al, 2015); (Giasson et al, 2015); (Teske et al, 2015a); (Teske et al, 2015b); (Vasques et al, 2015) 2016 (Arruda et al, 2016); (Bagatini et al, 2016); (Demattê et al, 2016); (Dias et al, 2016); (Henrique et al, 2016); (Pelegrino et al, 2016) 2017 (Chagas et al, 2017); (Wolski et al, 2017) 2018 (Costa et al, 2018); (Meier et al, 2018) 2019 (Campos et al, 2019a); (Campos et al, 2019b); (Moura-Bueno et al, 2019); (Silva et al, 2019); (Silvero et al, 2019) All learning algorithms were assigned to a type of classifier such as Artificial Neural Network (ANN), Bayes classifiers, Decision Tree (DT), Logistic Regression (LR) and Support Vector Machine (SVM). Approximately 95 % of the studies used DT, ANN and LR classifiers (Table 4).…”
Section: Descriptive Statistics Of the Data Extracted From The Studiesmentioning
confidence: 99%